ESTIMATION OF STATURE FROM LENGTH OF HAND IN VADODARA DISTRICT POPULATION (Journal of Forensic Medicine & Toxicology, 2016)
Stature or body height is one of the most important and useful anthropometric parameter that determine the physical identity of an individual. The study was done to estimate stature from the hand. The present study comprised of a sample of 200 healthy individuals (100 males and 100 females) studying in various places of Middle Gujarat Region. All the individuals were measured for height of body and length of hands. The data thus obtained have been subjected to statistical computation. Bilateral asymmetry in hand measurements were statistically insignificant. Regression equations were derived for right and left hand separately by which living stature may be fairly accurately estimated when a fragmentary or mutilated portion of upper extremity is recovered.
Keywords: anthropometric parameter; length; stature; regression equation